Suppose that x = log A and y = log B. i need to write these expressions in terms of x and y log(AB) log(A^3 times sqrt(B)) log(A-B)

chivistaelmore 2022-07-28 Answered
Suppose that x = log A and y = log B. i need to write these expressions in terms of x and y
log ( A B )
log ( A 3 × B )
log ( A B )
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

Minbutastc
Answered 2022-07-29 Author has 14 answers
log ( A B ) = log A + log B = x + y
log ( A 3 B ) = log A 3 + log B = 3 log A + 1 2 log B = 3 x + 1 2 y
log ( A B ) cant break it out
only work if it's log ( A ) log B = log A B

We have step-by-step solutions for your answer!

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

asked 2022-03-12
What is the simple way to show that
Nlog{N}klog{k}logk!{N!}
I tried to use the factorial and the log rules but..
Thanks.
asked 2022-04-26
simplify natural logarithm
How to simplify this natural logarithm
12ln|y+1|12ln|y1|+ln|C|=12ln|x+1|12ln|x1|
if I apply the logarithm rule
ln|y+1|ln|y1|+12ln(C2)=ln|x+1|ln|x1|
Please help further..
asked 2022-09-19
Evaluate 1 ln ( 2 x 1 ) x 2
My approach is to calc
1 X ln ( 2 x 1 ) x 2 d x
and then take the limit for the answer when X
However, I must do something wrong. The correct answer should be 2 ln ( 2 )
1 X ln ( 2 x 1 ) x 2 d x = [ 1 x ln ( 2 x 1 ) ] 1 X + 1 X 1 x × 2 2 x 1 d x = 1 X ln ( 2 X 1 ) + 2 1 X 1 x + 2 2 x 1 d x = 1 1 X ln ( 2 X 1 ) 2 ln X + 2 ln ( 2 X 1 )
Am I wrong? If I'm not, how to proceed?
=== EDIT ===
After the edit I wonder if this is the correct way to proceed:
1 X ln ( 2 X 1 ) 2 ln X + 2 ln ( 2 X 1 )
The first part will do to zero because of 1 X so we ignore that one, the second and third part:
2 ln X + 2 ln ( 2 X 1 ) = 2 ln ( 2 X 1 X ) = 2 ln ( 2 1 X ) = 2 ln ( 2 )
asked 2022-04-30
Logarithmic equations and their related exponential equations
I am learning about logarithms and I'd like some examples of the following:
Examples where the logarithmic value is a different positive integer
Examples where the logarithmic value is a different negative integer
Examples where the logarithmic value is a different non-integer fractional value
asked 2022-07-05
asked 2021-12-30
What is ln(ex)?
asked 2022-07-08
How does 7 log ( 8 x ) = 7 ln 8 x
I was working on some math homework with a program called scientific notebook. I was check that
I was writing something correctly.
The original equation is ( log ( x 4 ) + log ( x 5 ) ) / log ( 8 x ) = 7
I then converted it to log ( x ( 4 + 5 ) ) = 7 log ( 8 x )
I was expecting to get log ( ( 8 x ) 7 ) when I entered the 7 log ( 8 x ) into the program to evaluate. Can someone please explain this to me?

New questions